TES PROVOKASI (TP) SEBAGAI UPAYA PENDEKATAN DIAGNOSIS DUGAAN ALERGI OBAT PADA SEORANG PENDERITA TB PARU YANG DITERAPI DENGAN OBAT ANTI TUBERKULOSA KATEGORI I - Duarsa, Reny S.P.; Suryana, Ketut (journal of internal medicine; Vol. 7, No. 3 September 2006)
Drug allergy is an unpredictable adverse reaction which is based on immunologic reaction. This event accounts for around 5 to 10 % of the total number of adverse reaction to drug events. Diagnostic approaches to drug allergy are based on detailed anamnestic questions, chronology of events, physical diagnostics and are also supported by other examinations such as skin prick test, skin patch test, radioallergosorbens test (RAST) and drug provocation test (DPT). DPT is still the gold standard for drug allergy test and is done if other tests cannot confirm a significant conclusion. Nonetheless, this procedure is a dangerous course of action. Hence close coordination with intensive care unit and retaining informed consent should be done ahead of time. In this paper, we will examine a specific case in which DPT test is used to find out the drug which had caused an allergic reaction. It is shown in this paper, we are able to conduct a safe diagnostic procedure as long as we take into consideration the risk and benefit for each patient. In this paper, we also point out about indication, contraindication, when to perform the test, test method, interval - dose, test preparation, and what kind of conclusion could be taken from the test.
Keywords: provocation test, drug allergy, TB drug